2014
DOI: 10.1371/journal.pone.0101026
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Urinary Levels of Cystatin C and Neutrophil Gelatinase-Associated Lipocalin in Henoch-Schönlein Purpura Patients with Renal Involvement

Abstract: Henoch-Schönlein purpura (HSP) is a commonest systemic vasculitis in childhood. The long-term prognosis of HSP is determined by the degree of renal involvement. The aim of this study is to search novel clinically applicable biomarkers to evaluate renal involvement in HSP patients. 20 bio-indexes in urine samples were simultaneously screened by antibody array assay. We indicated that urinary levels of cystatin C (Cys C) and neutrophil gelatinase-associated lipocalin (NGAL) in HSP patients with renal involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
2
3
1
1
Order By: Relevance
“…Nevertheless, as opposed to our study this particular research revealed that its levels were higher in urine of IgAV‐N patients, compared with IgAV‐noN patients and negatively correlated with eGFR 6 . In a separate study, through examining children and young adults, Chen et al suggested that urinary NGAL may be a novel useful biomarker of renal involvement in patients with IgAV 7 . However, the conclusion of research conducted on children by Pillebout et al indicated NGAL was not a discriminating biomarker of nephritis, thus corroborating the results obtained in our study 19 .…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, as opposed to our study this particular research revealed that its levels were higher in urine of IgAV‐N patients, compared with IgAV‐noN patients and negatively correlated with eGFR 6 . In a separate study, through examining children and young adults, Chen et al suggested that urinary NGAL may be a novel useful biomarker of renal involvement in patients with IgAV 7 . However, the conclusion of research conducted on children by Pillebout et al indicated NGAL was not a discriminating biomarker of nephritis, thus corroborating the results obtained in our study 19 .…”
Section: Discussioncontrasting
confidence: 91%
“…Encouraged by recently published promising reports presenting the value of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) in distinguishing patients with IgAVN [6][7][8][9][10] as well as manuscripts on the role of the liver-fatty acid binding protein (L-FABP) as a novel biomarker of kidney injury, [11][12][13] we decided to evaluate their concentrations in children with IgAV.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published on the predictive value of NGAL in acute renal injury (e.g., cardiac surgery, contrast-induced nephropathy, kidney transplantation). In IgAV patients, urinary NGAL seems to distinguish adult patients with or without nephritis [ 35 ] similarly to children [ 36 ]. An increased serum NGAL concentration was present in both IgAV-N and IgAV-woN children in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Bir başka çalışmada 43 HSP'lı hastanın serumundaki visfatin (pre-B-hücresi koloni uyarıcı faktör) düzeyi 45 kontrol serumu ile kıyaslanmış ve visfatin düzeyi renal tutulumun bulunduğu hastalarda anlamlı derecede yüksek bulunmuş, ayrıca iyileşme sonrası bu yükselmenin normal seviyeye indiği göz-lenmiştir 28 . HSP'lı hastaların kontrol grubu ve atopik dermatitli hasta grubu ile karşılaştırıldığı bir çalışmada ise idrarda bakılan Sistatin C ve Nötrofil jelatinaz ilişkili lipokalin (NGAL) düzeyleri HSP nefriti bulunan hastalarda belirgin yüksek bulunmuştur 29 . Türkiye'de yapılmış bir çalışmada ise nötrofil-lenfosit oranının (NLR) yüksekliği ve ortalama platelet hacminin (MPV) düşük-lüğü HSP'lı hastalardaki gastrointestinal kanama ile pozitif iliş-kili bulunmuştur 30 .…”
Section: Discussionunclassified